Periosteal pedicle graft for the treatment of gingival recession defects current status and future prospects: What the evidence suggests? - Ajay Mahajan; Kanwarjit Singh Asi (Wolters Kluwer Medknow Publications, 2016)
Background: Gingival Recession defects are one of the most common defects for which patients seek periodontal treatment. Many treatment options are available for the management of gingival recession .Most of the treatments offered aim to treat the cause, cover the denuded root surface and produce a long term aesthetic result. The use of periosteal pedicle graft (PPG) is a recent innovation for the treatment of gingival recession defects and has gained much attention in a short span of time. Although studies have been done utilizing PPG successfully for the treatment of gingival recession defects (GRD) but it is still not clear, whether PPG technique should be included in the established list of techniques used to treat GRD? An effort has been made to arrive at a decision on the current utility of PPG in the treatment of GRD based on the scientific evidence available in literature. Materials and Methods: A review of current literature was done to critically evaluate the evidence related to the Periosteal pedicle graft technique. Results and Conclusion: Periosteal Pedicle Graft has come up as a viable treatment option for the treatment of GRD although it's still too early to predict the long-term results associated with PPG.